Neutronic and Thermalhydraulic Evaluation of Annular Fuel in PWR with Three Different Nanofluids - Ali Tiftikçi (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In pressurized nuclear reactors, one of the fuel design principles is the fuel centerline temperature limit. Since the thermal conductivity of UO2 is not high, the temperature increases rapidly from the fuel surface to the fuel center. To overcome this limitation, the use of annular type fuels instead of solid fuels is one of the improvement efforts. In this study, the effects of using annular fuel in a typical PWR are investigated. At the same time, the effects of adding nanoparticles (〖Al〗_2 O_3,Cu and TiO_2) to the coolant water in the case of solid and annular fuels are also investigated. For both cases, neutronic and thermalhydraulic calculations are made and compared. In neutronic point of view, it has been shown that the use of annular fuel does not cause a significant change in the k_eff value but the presence nanoparticles reduces the k_eff. This reduction is maximum for Cu+water and minimum for 〖Al〗_2 O_3+water nanofluids. In thermalhydraulic point of view, it has been shown that the annular fuel positively affects the fuel temperature limits and the addition of nanoparticles could provide an additional contribution to this, provided that it is in very small amounts (φ